Peran Teknologi Informasi dalam Pembentukan Output Daerah: Studi Empiris di Pulau Jawa Tahun 2019–2023: Indonesia - wijayanti, diana (Asian Journal of Innovation and Entrepreneurship, 2025)
This study aims to analyze the role of Information and Communication Technology (ICT), Foreign Direct Investment (FDI), and the Human Development Index (HDI) in shaping regional output in five provinces on the island of Java. The method used is panel data regression with a random effects approach, where ICT, FDI, and HDI are the independent variables, while Gross Regional Domestic Product (GRDP) is the dependent variable. The results show that all three variables have important and complementary roles in driving GRDP during the 2019–2023 period, but ICT has the most significant influence compared to HDI and FDI. This reflects the high technological advancement in Java and the crucial role of ICT in the region's economic growth. Practically, this study recommends strengthening digital infrastructure, improving the quality of human resources through technological literacy, optimizing FDI based on technology transfer, and accelerating digital transformation in the local economic sector through the development of a regional digital economy blueprint to encourage inclusive and sustainable growth. These findings are expected to enrich the literature and serve as a strategic policy reference for local governments in increasing GRDP in the five provinces on the island of Java.